The Ringed Kingfisher, Ceryle or Megaceryle torquata (Cerylinae, Alcedinidae, Coraciiformes)? An osteological view - Pascotto, Marcia Cristina; Hofling, Elizabeth; Donatelli, Reginaldo José [UNESP] (Neotropical Ornithological Society, Usgs Patuxent Wildlife Research Center, 2006)
In spite of the unquestionable monophyly of die Cerylinae subfamily, there are divergences in considering Megaceryle torquata in die genera Megaceryle or Ceryle. In order to address the question, here is a comparative osteological study between M. torquata and C. rudis, as well as with the other Megaceryle species and Chloroceryle. The findings showed more osteological similarities between M. torquata and the other Megaceryle species, differing considerably of C. rudis. Also, the data have permited the identification of the genus Megaceryle, with most of the characters from the skull. In spite of not having any phylogenetic inference, there are relevant osteological evidences that permit the consideration of M. torquata in the genus Megaceryle and the maintenance of Ceryle only for reception of C. rudis. Accepted 19 June 2006.
Keywords: Ringed Kingfisher; Ceryle; Megaceryle torquata; Cerylinae; Alcedinidae; Coraciiformes; osteology; systematic